2008
DOI: 10.1007/s10765-008-0475-0
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Prediction of Quench Energies of Cooled Superconductors Based on the Hyperbolic Heat Conduction Model

Abstract: The critical energy characteristics of cooled composite superconductors is analytically predicted based on the one-dimensional hyperbolic heat conduction model. The temperature dependence of the Ohmic heat generation, the finite speed of heat transfer, and the finite duration and finite length of the thermal disturbances are taken into account in the present model. The critical energies are calculated using a model based on the analytical solution of the hyperbolic heat conduction equation by the Laplace trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Their results also showed that some obvious differences on MQE with the increasing of thermal relaxation time and operation current in the superconductors by comparing the results with the ones from the classical Fourier heat conduction theory. Al-Odat and his coworkers [24,25] further studied the critical energy characteristics of cooled composite superconductors based on an one-dimensional hyperbolic heat conduction model, and their computational results showed that the critical energy depends on the relaxation time and disturbance duration. It was found that the hyperbolic heat conduction model predicted a lower-critical energy comparing with the ones of the parabolic heat conduction model.…”
Section: Introductionmentioning
confidence: 99%
“…Their results also showed that some obvious differences on MQE with the increasing of thermal relaxation time and operation current in the superconductors by comparing the results with the ones from the classical Fourier heat conduction theory. Al-Odat and his coworkers [24,25] further studied the critical energy characteristics of cooled composite superconductors based on an one-dimensional hyperbolic heat conduction model, and their computational results showed that the critical energy depends on the relaxation time and disturbance duration. It was found that the hyperbolic heat conduction model predicted a lower-critical energy comparing with the ones of the parabolic heat conduction model.…”
Section: Introductionmentioning
confidence: 99%
“…The Fourier law, which states that heat is transferred by diffusion process alone, cannot account for the transient heat transfer in situations such as extremely short time duration, very low temperature, and extremely large heat flux. Hence, there has been a growing interest in discovering new heat transfer models [7] as well as applying existing non-Fourier models to physical problems [2,13,24]. Most recent examples include but not limited to the application of non-Fourier heat transfer to study laser-induced thermal damage in biological tissues with nonhomogeneous inner structures [24], to investigate the critical energy characteristics of cooled composite superconductor [2], and to examine the physical anomalies during the transient heat transfer process under the dual-phase-lag model [13].…”
Section: Introductionmentioning
confidence: 99%